Museum Libraries and Their Contributions to Museum Information Environment - Mollaoglu, R. Neslihan (TURKISH LIBRARIANS ASSOC, 2007)
Museum Libraries is a kind of special library owing to the fact that it gives service to the environment of the museum and improves the collection related to the specialization of the museum that they connected to. Museums going toward the service approach based on knowledge from the service approach based on object enlarged the museum libraries' service areas. This article deals with museum libraries as one of the elements that completes the museum information area and aims to question the contributions that they could make by introducing its functions and determine the status over the selected examples. In this context, 7 museum libraries from abroad and 11 museum libraries in the country are investigated in the field of their infrastructural conditions and services that they present to their users. It is concluded that the activity areas of the museum libraries are connected to the approach of the museology that they adopt and its conditions are determined in the direction of the management departments that they linked with
Keywords: Museum libraries; Museum information services; Museum information environment; Information Science & Library Science